2021
DOI: 10.3389/fimmu.2021.760475
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Spätzle5 in Antimicrobial Peptide Production Against Escherichia coli in Tenebrio molitor Malpighian Tubules

Abstract: The dimeric cytokine ligand Spätzle (Spz) is responsible for Toll pathway activation and antimicrobial peptide (AMP) production upon pathogen challenge in Tenebrio molitor. Here, we indicated that TmSpz5 has a functional role in response to bacterial infections. We showed that the highest expression of TmSpz5 is induced by Candida albicans. However, TmSpz5 knockdown reduced larval survival against Escherichia coli and Staphylococcus aureus. To evaluate the molecular mechanism underlying the observed survival d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Complexes of spz and Toll proteins arrange hetero-trimers consisting of MyD88, Tube, and Pelle, which are intracellular components of the Toll pathway, leading to the expression of Toll-pathway-dependent AMPs (e.g., drosomycin) [ 10 , 11 , 23 , 24 ]. These involvements of Toll and spz in AMP production were reported in Bombyx mori (Lepidoptera; Bombycidae, Linnaeus, 1758) , Tenebrio molitor (Coleoptera; Tenebrionidae, Linnaeus, 1758), and Manduca sexta (Lepidoptera; Sphingidae, Linnaeus, 1763) [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 76%
“…Complexes of spz and Toll proteins arrange hetero-trimers consisting of MyD88, Tube, and Pelle, which are intracellular components of the Toll pathway, leading to the expression of Toll-pathway-dependent AMPs (e.g., drosomycin) [ 10 , 11 , 23 , 24 ]. These involvements of Toll and spz in AMP production were reported in Bombyx mori (Lepidoptera; Bombycidae, Linnaeus, 1758) , Tenebrio molitor (Coleoptera; Tenebrionidae, Linnaeus, 1758), and Manduca sexta (Lepidoptera; Sphingidae, Linnaeus, 1763) [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 76%
“…This protein is a zymogen and is cleaved to its mature form by a chain of serine protease activation, following pathogen recognition by PRRs (24,57). The immunological roles of Spz isoforms (Spz1b, Spz-like, Spz4, Spz5, and Spz6) in T. molitor have been investigated using RNAi (58)(59)(60)(61)(62). Among them, TmSpz1b, TmSpz-like, and TmSpz5 showed anti-Gramnegative bacterial (E. coli) activity (58,61,62).…”
Section: Cross-regulation Of Imd and Toll Pathways In T Molitormentioning
confidence: 99%
“…The immunological roles of Spz isoforms (Spz1b, Spz-like, Spz4, Spz5, and Spz6) in T. molitor have been investigated using RNAi (58)(59)(60)(61)(62). Among them, TmSpz1b, TmSpz-like, and TmSpz5 showed anti-Gramnegative bacterial (E. coli) activity (58,61,62). silencing of TmSpz1b downregulated the expression of TmDorX1 and TmRel in the immune organs (58).…”
Section: Cross-regulation Of Imd and Toll Pathways In T Molitormentioning
confidence: 99%
See 1 more Smart Citation
“…The first article of this Research Topic ( Bae et al ) discusses the anti-Gram-negative function of another Toll ligand spätzle 1b (TmSpz1b) identified from the RNA sequencing database of T. molitor . Other studies, reported by the same research group, have critically characterized the function of T. molitor spätzle isoforms such as spätzle 5 (TmSpz5) and spätzle 6 (TmSpz6) in regulating AMP production in the Malpighian tubules in response to Escherichia coli , and against E. coli and Staphylococcus aureus , respectively ( Edosa et al, 2020 ; Ali Mohammadie Kojour et al, 2021 ). TmSpz1b was characterized as a secretory protein with a conserved cystine-knot domain as evidenced in other insects including spätzle protein in Drosophila melanogaster .…”
mentioning
confidence: 99%